2015
DOI: 10.4103/0972-4052.159970
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of marginal fit and internal adaptation of zirconia copings fabricated by two CAD - CAM systems: An in vitro study

Abstract: Statement of Problem:Three main factors which determine the success of an All-ceramic restoration are esthetic value, resistance to fracture and third being the marginal fit. Marginal fit and internal adaptation are crucial factors in increasing the longevity of the restoration. Newer and economical CAD CAM systems have been introduced claiming better marginal fit and adaptation of All ceramic crowns. CAD CAM systems involves scanning of the die or the tooth preparation and milling of the restoration, which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
0
15
0
3
Order By: Relevance
“…However, this study made use of an Etkon milling center and a traditional silicone impression technique rather than an intraoral scanner. Studies that compared marginal fit of zirconia coping found that the CEREC inLAB system showed smaller MD values compared to other CAD-CAM systems [15, 16, 22]. Rajan et al compared the marginal fit of zirconia coping produced by CEREC inLAB with that of the CERAMILL system and found significant differences, whereby CEREC inLAB copings had better adaptation than CERAMILL.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this study made use of an Etkon milling center and a traditional silicone impression technique rather than an intraoral scanner. Studies that compared marginal fit of zirconia coping found that the CEREC inLAB system showed smaller MD values compared to other CAD-CAM systems [15, 16, 22]. Rajan et al compared the marginal fit of zirconia coping produced by CEREC inLAB with that of the CERAMILL system and found significant differences, whereby CEREC inLAB copings had better adaptation than CERAMILL.…”
Section: Discussionmentioning
confidence: 99%
“…Rajan et al compared the marginal fit of zirconia coping produced by CEREC inLAB with that of the CERAMILL system and found significant differences, whereby CEREC inLAB copings had better adaptation than CERAMILL. For both CAD-CAM systems, a digital scanner was used [22]. Marginal fit for CERAMILL was 83 μm and for the CEREC InLAB MC XL was 68 μm [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in view of the fact that the experimental procedure was the only part of all the production process for actual restoration, these resultant data only reflected the degree of deviation between virtual reference object and prepared tooth test datasets in this study. Thus, the methodology of this study was different from many previous literatures, 23 24 25 26 27 28 which described the adaptation of prostheses was the gaps between the real restoration and the abutment tooth.…”
Section: Discussionmentioning
confidence: 94%